The Musical Language in Messiaen’s Catalogue d’oiseaux - Loo Fung Chiat; Loo Fung Ying (Muzikološki Zbornik, 2019)
This paper presents an analysis of Olivier Messiaen’s ‘La Chouette hulotte’ from Catalogue d’oiseaux. The significance of this work lies in the representation of fear by the owls and ‘night’ music. Messiaen’s language of mode de valeurs representing the ‘night’ and the harmonic language of the tawny owl’s calls identifies Messiaen’s music.